Effect of infill pattern and infill density on mechanical behaviour of FDM 3D printed Parts- a current review. (2022) - Qamar Tanveer, Md.; Mishra, Gautam; Mishra, Siddharth; Sharma, Rohan
Abstract: Additive Manufacturing (AM) offers flexibility in customising, designing, minimising waste, faster prototyping and manufacturing complex profiles. The process parameters play a crucial role in the mechanical strength of the 3D printed product. The paper's objective is to provide a concise review of additive manufacturing techniques, focusing on the Fused Deposition Method (FDM) and its process parameters, mainly infill pattern and infill density and its effect on the physical behaviour of 3D printed parts. The article also includes the functional and industrial applications of rapid prototyping. The article's contribution is to explain to the researchers from academics and industry how and why infill density and infill pattern affect the mechanical properties of the 3D printed part.